A distributed trust mechanism for malicious behaviors in VANETs - Ali Kamil Ahmed; Mohanad Najm Abdulwahed; Behnam Farzaneh (Institute of Advanced Engineering and Science, 2020)
Vehicular ad-hoc networks (VANETs) are one of the most important types of networks which are widely used in recent years. Along with all the benefits of quality of service (QoS) improvements, vulnerability analysis for this type of networks is an important issue. For instance, a gray-hole attack decreases network performance. We proposed a novel solution to help to secure these networks against this vulnerability. The proposed method can detect and prevent the gray-hole attack. Anywhere in the network, each node (vehicle) can distinguish between the gray-hole attack and the failed link. Some topology related information helps us to detect attacks more accurately. Also, the proposed method uses the most reliable path in terms of link failure when there is no malicious node. In this paper, we used the TOPSIS method for choosing the most trusted node for routing intelligently. We validated our proposal using a simulation model in the NS-2 simulator. Simulation results show that the proposed method can prevent Gray-hole attack efficiently with low overhead.